2016
DOI: 10.5588/ijtld.16.0048
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of thrice-weekly rifampicin, isoniazid and pyrazinamide in adult tuberculosis patients in India

Abstract: Several risk factors for drug concentration variations were identified. Two-hour post-dosing drug concentrations mimicked Cmax. A high proportion of TB patients had RMP Cmax below the expected range, which is a matter of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 16 publications
2
39
2
Order By: Relevance
“…In contrast to adults, data on isoniazid elimination clearance in children are scarce. The median simulated AUC 0–8 obtained in this study was 25.53 [interquartile range (IQR) 18.22–31.76], which is much lower compared to the median AUC 0–8 of 41.1 (IQR 33.0–59.9) obtained in an adult population in a study from India . One of the limitations of the present study is that the acetylator status of the children is not known.…”
Section: Discussioncontrasting
confidence: 79%
“…In contrast to adults, data on isoniazid elimination clearance in children are scarce. The median simulated AUC 0–8 obtained in this study was 25.53 [interquartile range (IQR) 18.22–31.76], which is much lower compared to the median AUC 0–8 of 41.1 (IQR 33.0–59.9) obtained in an adult population in a study from India . One of the limitations of the present study is that the acetylator status of the children is not known.…”
Section: Discussioncontrasting
confidence: 79%
“…This effect was not mitigated after adjusting for other factors. These results are in keeping with the results from other studies that reported lower pyrazinamide and isoniazid C max concentrations in DM patients in the intensive phase, even after adjusting for possible confounders (23,25).…”
Section: Discussionsupporting
confidence: 92%
“…A few studies have evaluated the effect of DM on the pharmacokinetics (PK) of antituberculosis drugs, and the results have been mixed, with some reporting lower anti-TB drug concentrations in people with DM (17)(18)(19)(20) and others showing no effect of DM on first-line drug exposures (21)(22)(23). In the context of a large prospective cohort study involving patients with and without DM in India, we evaluated the effects of DM (and the HbA1c value) on first-line anti-TB drug pharmacokinetics.…”
mentioning
confidence: 99%
“…Since this study was undertaken in programmatic settings, we chose to estimate the drug concentrations at 2 h postdosing, which is predictive of the pharmacokinetic parameters obtained from intensive sampling (12). We have shown that the RMP, INH, and PZA concentrations at 2 h postdosing correlate with the peak concentrations and are often used as a surrogate for peak concentrations, though this sample does not account for slow drug absorption (13).…”
Section: Discussionmentioning
confidence: 99%